62.2: Invited Paper: Bridged‐Grain Polycrystalline Silicon Thin‐Film Transistors. Issue 1 (1st July 2013) - Kwok, Hoi‐Sing; Zhou, Wei; Chen, Rongsheng; Zhao, Shuyun; Zhang, Meng; Wong, Man; Chen, Shuming; Chow, Thomas
Abstract: A new structure for thin‐film transistors is proposed and demonstrated, exhibiting the benefits but not the drawbacks of both short‐channel and multi‐junction effects. Simulations are performed to verify the physics of this device structure. All characteristics such as threshold voltage, pseudo subthreshold slope, on‐off current ratio and field‐effect mobility are improved.